Measuring patient safety culture in Chinese hospitals using the Hospital Survey on Patient Safety Culture (HSOPSC) - Qianying Zhang (2022)
Background: Patient safety issues have received widespread attention all over the world. Measuring patient safety culture is an important part to manage and improve patient safety. Objective: The purpose of this research is to test the validation of the Hospital Safety on Patient Safety Culture (HSOPSC) scale in the Chinese healthcare setting. Method: This study used a sample of 2465 from a medical group. The following analysis methods were employed to understand the validity of the HSOPSC scale and the patient safety culture issues in the medical group: Exploratory Factor analysis (EFA) was performed to examine the applicability of the factor structure of the original questionnaire to the HM Hospital Group data. Two-sample T test and One-way ANOVA for discrimination according to variable conditions and Pearson's correlation also were conducted to understand the patient safety issues in Chinese hospitals. Result: This study indicates towards a 7-factor model instead of the 10-dimenion HSOPSC scale. This study also identifies some cultural issues of using SPOPSC in Chinese hospital setting which will compromise the applicability of this instrument. Conclusion: Cautions should be taken when using SPOPSC in Chinese hospitals. In addition, measuring patient safety culture in Chinese hospital per se is challenging due to the national culture.